Evaluasi Kepuasan Peserta Pelatihan terhadap Kinerja Widyaiswara dan Fasilitas Pelatihan di BPSDM Aceh - Nurlia, Nurlia (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2020)
This study aimed to determine trainee evaluation toward two aspects, the first was trainer’s (Widyaiswara) teaching performance and, the second was training facilities in Human Resources Development Agency (Badan Pengembangan Sumber Daya Manusia/BPSDM) of Aceh. The research method used was descriptive qualitative. There were 76 respondents which were taken from trainees of middle and lower level leadership trainings in BPSDM Aceh during financial year of 2018. Data were analyzed qualitatively and explained descriptively to answer research questions. The results showed that, in general, respondents rated trainer’s (Widyaiswara) teaching performance with good mark (82-90 points from 100 scale). Meanwhile evaluation result for training facilites in BPSDM Aceh were ranged from 9%(poor), 23%(adequate), 47%(good), and 21%(satisfactory). In conclusion, teaching performance during leadership training was good. Respondents found that study room and learning facilites were meet their expectation, on the other hand, residential dormitory was perceived unsatisfyingly.